EVALUASI PROGRAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL SMP/MTS DI KOTA BIMA - Waluyati, Ida (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2012)
Penelitian ini bertujuan untuk mengetahui kesesuaian pelaksanaan program pembelajaran IPS SMP/MTs di Kota Bima, yang meliputi: 1) perencanaan, 2) pelaksanaan, dan 3) penilaian serta tindak lanjutnya, 4) dan hasil pembelajaran kognitif IPS siswa dengan standar Kriteria Ketuntasan Minimal belajar. Penelitian ini merupakan penelitian evaluasi dengan meng-gunakan Model Countenance Stake, yang meliputi evaluasi Antecedents, Transac-tions, dan Outcomes. Subjek penelitian adalah 78 guru IPS yang diambil secara populasi dan siswa sejumlah 390 orang yang dipilih secara Quota Stratified Random Sampling. Teknik pengumpulan data yang digunakan adalah angket, tes, dan dokumentasi. Instrumen yang digunakan adalah kuesioner, tes, dan daftar cek. Analisis data dilakukan dengan analisis deskriptif kuantitatif, dengan membandingkan hasil penelitian dengan kriteria yang telah ditentu-kan. Hasil penelitian menunjukkan bahwa kesesuaian antara pelaksanaan program pembelajaran IPS SMP/MTs di Kota Bima dengan standar proses pendidikan adalah sebagai berikut : (1) Perencanaan pembelajaran berada pada kategori baik (sesuai), (2) Proses pembelajaran berada pada kategori cukup baik (cukup sesuai), (3) Penilaian hasil belajar serta tindak lanjut hasil penilaian berada pada kategori baik (sesuai), (4) dan hasil belajar kognitif IPS siswa berada pada kategori baik (sesuai) standar Kriteria Ketuntasan Minimal belajar. Kata kunci: evaluasi program, pembelajaran IPS______________________________________________________________ EVALUATION OF SOCIAL STUDIES INSTRUCTIONAL PROGRAM FOR JUNIOR HIGH SCHOOL/MADRASAH TSANAWIYAH IN BIMA REGENCY Abstract This study aims to evaluate the implementation of social studies instructional program for Junior High School/Madrasah Tsanawiyah in Bima regency, which involves: (1) planning, (2) implementation process, (3) learning outcome assessments and its follow-up with education process standard, (4) and students cognitive learning outcomes with learning minimal criteria standard. This is an evaluation research study employing the Countenance Stake's model consisting of the evaluation of antecedents, transactions, and outcomes. The subjects of this study were 78 social studies teachers of Junior High School/Madrasah Tsanawi-yah in Bima regency selected through population techniques and 390 students through quota stratified random sampling. The data were collected by using questionnaires, test and documentation techniques. The validity of the Instru-ments was done through logical. The questionnaire reliability was calculated by using Alpha Cronbach, while the questionnaires validity used content validity technique from expert and it was calculated by using Product Moment Corellation. Reliability coefficient of the questionnaires in terms of social studies instructional implementation process is 0.842 and learning outcome assessments and its follow-up is 0.772. Based on test results, all the instruments are valid and reliable. The data are analyzed by using the quantitative descriptive analysis by comparing the results of this research with the predetermined criteria. Data analysis result shows that the implementation of the social studies instructional program for Junior High School/Madrasah Tsanawiyah in Bima regency with the education process standard, is as follows. (1) The instructional plan is in good (compatible)category. (2) The instructional process is in quite good (quite compatible) category. (3) The learning outcome assessments and its follow-up is in good (compatible) category. (4) students cognitive learning outcomes is in good (compatible) category with the learning minimal criteria standard. Keywords: program evaluation, social studies instructional